Nanosheets, applications and preparation methods thereof

By synthesizing nanosheets with superlattice structure in solution, using the epitaxially grown second semiconductor compound shell layer to achieve directional two-dimensional connection of semiconductor nanocrystals, the problem of difficult quantum coupling between colloidal quantum dots is solved, and the problem of quantum coupling between colloidal quantum dots is realized. The preparation of high-quality nanosheets has excellent optical properties.

CN115975622BActive Publication Date: 2025-02-11ZHEJIANG UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111196162.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-14
Publication Date
2025-02-11
Estimated Expiration
2041-10-14

AI Technical Summary

Technical Problem

The prior art is difficult to achieve quantum coupling between colloidal quantum dots, resulting in the generated structure being unsuitable for application under normal temperature conditions, and there are defect states or bound energy levels introduced by structural defects, which affect photogenerated carriers and electrogenerated carriers. performance.

Method used

By synthesizing nanosheets with superlattice structures in solution, the epitaxially grown second semiconductor compound shell is used to achieve directional two-dimensional connection of semiconductor nanocrystals to form a continuous single crystal matrix, and quantum coupling between semiconductor nanocrystals is achieved. .

Benefits of technology

A high-quality nanosheet has been achieved, with fluorescence efficiency of greater than or equal to 50%, and a half-maximum width of less than or equal to 105meV. It has uniform optical characteristics and is suitable for application under normal temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115975622B_ABST
    Figure CN115975622B_ABST
Patent Text Reader

Abstract

The present disclosure provides a nanosheet and a preparation method thereof, an optoelectronic device containing the same, and a nanosheet dispersion. The nanosheet includes a plurality of semiconductor nanocrystals distributed at intervals and a matrix in which the plurality of semiconductor nanocrystals are dispersed. The material of the semiconductor nanocrystals is a first semiconductor compound, and the material of the matrix is ​​a second semiconductor compound, and the matrix is ​​a continuous single crystal material. The semiconductor nanocrystals are dispersed at intervals in a two-dimensional matrix, and the second semiconductor compound formed by epitaxy is not only continuous and complete without voids, but also has good crystallization quality and is in a single crystal state. Such a matrix crystal, on the one hand, limits the spatial distribution of electrons and holes of the semiconductor nanocrystals, and also provides a basis for quantum coupling between semiconductor nanocrystals. And the newly formed nanosheet realizes the characteristics of uniform optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of nanosheet preparation, and in particular to a nanosheet, an application and a preparation method thereof. Background Art

[0002] Colloidal quantum dots (QD) are also called "artificial atoms". Their electronic structure can be mainly described by quantum-confined exciton states. The exciton wave function is basically confined in space inside the quantum dots, and a small part can overflow the surface of the quantum dots. When the quantum dots are close to each other, the exciton states of different quantum dots can be coupled. When multiple quantum dots achieve quantum coupling, a new type of semiconductor material can be obtained, that is, a superlattice with a mini-band. Superlattices have aroused great interest in people due to their unique electronic, optical and optoelectronic properties, and great efforts have been made in the preparation of superlattices. .

[0003] Although superlattices of self-organized quantum dots have been fabricated on single-crystal substrates by molecular beam epitaxy and other high-vacuum techniques, the control of the size distribution of self-organized quantum dots and the spacing between quantum dots is far from precise, and the spatial confinement of excitons provided by the matrix material around the quantum dots is usually weak, which makes the resulting structure unsuitable for application at room temperature. In contrast, colloidal quantum dots can achieve nearly monodisperse electronic structures, and the matrix materials (wide-bandgap semiconductor shells and organic ligands) have very strong spatial confinement of excitons, but it is still challenging to achieve controllable quantum coupling between colloidal quantum dots. Colloidal quantum dots can be assembled into ordered three-dimensional and two-dimensional structures through ligand-ligand interactions between adjacent quantum dots, but organic ligands effectively decouple the exciton wave functions of individual quantum dots. Colloidal PbSe quantum dots can be formed into two-dimensional thin films by epitaxial splicing and fusion on solid or liquid substrates, but there are many honeycomb structures filled with residual ligands and air in them, which restrict the spatial distribution of excitons. In order to improve the film quality, CdSe / CdS core-shell quantum dots with high luminescence efficiency are prepared by filling non-epitaxially grown CdS and / or ZnS lattices between adjacent quantum dots. Unfortunately, measurements and calculations have confirmed that quantum coupling between quantum dots has not yet been achieved due to the uneven distance between adjacent quantum dots, lattice disorder of the connecting material, and point defects near the holes. In addition, these structural defects also introduce defect states or bound energy levels in the quantum dot solid / film, affecting the photogenerated and electrogenerated carriers. For example, CdSe / CdS core-shell quantum dots with efficient photoluminescence on a substrate can be mostly quenched when CdS and / or ZnS are filled (non-epitaxially). Summary of the invention

[0004] The purpose of the present disclosure is to provide a high-quality nanosheet with unique photoelectric properties and a preparation method and application thereof.

[0005] According to a first aspect of the present disclosure, a nanosheet is provided, comprising a plurality of spaced-apart semiconductor nanocrystals and a matrix in which the plurality of semiconductor nanocrystals are dispersed, wherein the material of the semiconductor nanocrystals is a first semiconductor compound, the material of the matrix is ​​a second semiconductor compound, and the matrix is ​​a continuous single crystal material.

[0006] Furthermore, the second semiconductor compound has a different bandgap from that of the first semiconductor compound.

[0007] Furthermore, the first semiconductor compound and the second semiconductor compound have the same lattice structure, and the difference in lattice constant is less than 10%.

[0008] Furthermore, the first semiconductor compound is a II-VI compound, and the second semiconductor compound is a II-VI compound.

[0009] Furthermore, the first semiconductor compound is CdSe, the second semiconductor compound is CdS, wherein the molar content of cadmium in the nanosheets is 51-55%, the molar content of S is 35-40%, and the molar content of Se is 6-9%.

[0010] Furthermore, the distance between adjacent semiconductor nanocrystals is 1.2-3 nm.

[0011] Furthermore, the thickness of the nanosheet is in the range of 1.5 to 2.5 nm, and the lateral size of the nanosheet is in the range of 10 to 50 nm.

[0012] Furthermore, the thickness of the nanosheet is <001> The directions include 6-7 monolayers of Cd and 5 monolayers of Se / S.

[0013] Furthermore, the fluorescence emission peak of the above-mentioned nanosheet is between 500 and 520 nm.

[0014] Furthermore, the ultraviolet-visible absorption spectrum of the nanosheet includes a two-dimensional morphology absorption peak of the second semiconductor compound and a zero-dimensional morphology absorption peak of the first semiconductor compound.

[0015] Furthermore, the number of the semiconductor nanocrystal particles in the nanosheet is 10 to 1000.

[0016] Furthermore, the fluorescence efficiency of the nanosheet is greater than or equal to 50%, and the half-peak width is less than or equal to 105 meV.

[0017] According to a second aspect of the present disclosure, there is provided a photoelectric device, characterized in that it comprises the nanosheet according to any one of claims 1 to 12.

[0018] According to a third aspect of the present disclosure, a nanosheet dispersion is provided, comprising a plurality of nanosheets according to any one of claims 1 to 12 and a dispersion medium.

[0019] Furthermore, the thickness deviation between the above nanosheets is within 10%.

[0020] According to a fourth aspect of the present disclosure, a method for preparing a nanosheet is provided, the method comprising: preparing a stock solution containing a plurality of semiconductor nanocrystal cores of a first semiconductor compound; mixing the stock solution of the semiconductor nanocrystal cores and the raw material of a second semiconductor compound shell layer and heating them for reaction, thereby epitaxially growing the second semiconductor compound shell layer on the surface of each of the semiconductor nanocrystal cores to obtain core-shell semiconductor nanocrystals; utilizing the raw material of the second semiconductor compound shell layer to achieve directional two-dimensional connection of each of the core-shell semiconductor nanocrystals to obtain the nanosheet.

[0021] Furthermore, the above preparation method comprises:

[0022] S1, mixing a core cation precursor, a core anion precursor, an optional first ligand and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of the semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound;

[0023] S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor, the optional second ligand and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound;

[0024] S3, mixing the stock solution of the above-mentioned core-shell semiconductor nanocrystals, the cationic precursor for two-dimensional connection and the optional third ligand, and reacting them at a third temperature for a certain time, so that each of the above-mentioned core-shell semiconductor nanocrystals is two-dimensionally connected through the above-mentioned second semiconductor compound, to obtain a third dispersion containing the above-mentioned nanosheets; wherein the cations in the above-mentioned cationic precursor for two-dimensional connection are the cations in the above-mentioned second semiconductor compound.

[0025] Furthermore, the preparation method further comprises S4: separating and purifying the third dispersion to obtain nanosheets.

[0026] Furthermore, in the above S3, the above cationic precursor and the above optional third ligand are heated to a third temperature, and injected into the above stock solution of the core-shell semiconductor nanocrystals to mix and react.

[0027] Furthermore, in the above S3, the photoluminescence peak position of the product during the reaction does not undergo a blue shift.

[0028] Furthermore, the first temperature ranges from 210 to 260°C, the second temperature ranges from 170 to 190°C, and the third temperature ranges from 215 to 250°C.

[0029] Furthermore, the molar ratio of the shell cation precursor to the shell anion precursor in S2 is 5:4 to 5:1.

[0030] Furthermore, the molar ratio of each raw material in S2 is as follows: the molar ratio of the semiconductor nanocrystal in the above-mentioned stock solution containing the semiconductor nanocrystal core to the above-mentioned shell cation precursor is 1:50 to 1:200.

[0031] Furthermore, in the above S3, the stock solution of the above core-shell semiconductor nanocrystals, the anion precursor, the above cation precursor and the fatty acid are mixed and reacted at a third temperature to obtain a third dispersion containing nanosheets, wherein the anion in the above anion precursor is the anion in the second semiconductor compound.

[0032] Furthermore, the preparation method further comprises optimizing the surface of the nanosheets, thereby reducing surface defects of the nanosheets.

[0033] Furthermore, the first exciton absorption peak of the semiconductor nanocrystal core is located between 430 and 450 nm, and the first exciton absorption peak of the core-shell semiconductor nanocrystal is located between 470 and 490 nm.

[0034] Furthermore, the size of the semiconductor nanocrystal core is less than or equal to 2.5 nm, and the size of the core-shell semiconductor nanocrystal is less than or equal to 3.5 nm.

[0035] Furthermore, the core-shell semiconductor nanocrystal has a shell of 1 to 3 monolayers.

[0036] Furthermore, the conduction band energy of the shell layer is higher than the conduction band energy of the semiconductor nanocrystal core, and the semiconductor nanocrystal core is a zinc blende structure.

[0037] Furthermore, the fluorescence emission peak position of the nanosheet can be adjusted by adjusting one or both of the size of the semiconductor nanocrystal core and the shell thickness of the core-shell semiconductor nanocrystal.

[0038] Superlattice nanosheets were synthesized in solution by two-dimensional directional connection of pre-synthesized core-shell semiconductor nanocrystals. In addition to providing spatial confinement for the exciton state of semiconductor nanocrystals in the two-dimensional superlattice, the matrix also provides a single crystal state for the epitaxially grown nanosheets, which are dense and void-free, and better realize quantum coupling between semiconductor nanocrystals. This is also the basis for the uniform optical properties of two-dimensional superlattice nanosheets. The results show that semiconductor nanocrystals with unique and complex electronic structures can be obtained by a simple solution synthesis route, which is difficult to achieve by other methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings constituting a part of the present disclosure are used to provide a further understanding of the present disclosure. The exemplary embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute an improper limitation on the present disclosure. In the drawings:

[0040] Figure 1 A schematic diagram of the preparation process of the nanosheets disclosed in the present invention is shown.

[0041] Figure 2 (a) shows the UV-Vis and fluorescence emission (PL) spectra of the CdSe core in Example 1, Figure 2 (b) shows the HAADF diagram.

[0042] Figure 3 (a) shows the UV-Vis and photoluminescence (PL) spectra of the CdSe / CdS core-shell semiconductor nanocrystals in Example 1, Figure 3 (b) and HAADF plot.

[0043] Figure 4 The evolution of the HAADF graph at different reaction times during the reaction of the CdSe / CdS core-shell semiconductor nanocrystals to nanosheets in Example 1 is shown.

[0044] Figure 5 The evolution of the UV-Vis and fluorescence emission spectra of the reaction mixture during the oriented attachment in Example 1 at different reaction times is shown.

[0045] Figure 6 (a) shows a high-resolution HAADF top view of the nanosheet obtained in Example 1, Figure 6 (b) shows an atomic-resolution HAADF side view of the nanosheet.

[0046] Figure 7 (a) shows a high-resolution HAADF top view of the nanosheet obtained in Example 1, Figure 7 (b) shows a high-resolution HAADF side view of the nanosheet, with the inset being a local magnified view.

[0047] Figure 8 The fast Fourier transform (FFT) pattern of the nanosheets obtained in Example 1 is shown.

[0048] Fig. 9 The element distribution diagram of Cd, S and Se obtained by electron energy loss spectroscopy of the nanosheets obtained in Example 1 is shown.

[0049] Fig.10 Schematic diagrams of the top view (upper figure) and side view (lower figure) of the theoretical structure of the nanosheet obtained in Example 1 are shown.

[0050] Fig.11 X-ray diffraction patterns of the nanosheets obtained in Example 1 and the CdS nanosheets obtained in the comparative example are shown, and the inset is a Z (atomic number) contrast image of the nanosheets.

[0051] Fig.12 (a) shows the UV-Vis comparison of the CdSe / CdS core-shell semiconductor nanocrystals and nanosheets of Example 1,

[0052] Fig.12 (b) shows the comparison of fluorescence emission spectra of CdSe / CdS core-shell semiconductor nanocrystals and nanosheets.

[0053] Fig.13 The UV-Vis comparison diagram of the nanosheets of Example 1 and the CdS nanosheets obtained in the comparative example is shown.

[0054] Fig.14 (a) and (b) show the PL spectra comparison of single crystals and aggregates of two experimental batches of nanosheets obtained by the method of Example 1. Fig.14 (c) shows the statistical graph of the fluorescence peak position and fluorescence half-peak width of single crystals and aggregates of nanosheets from different experimental batches obtained by the method of Example 1.

[0055] Fig.15 (a) shows the photoexcitation spectra of the CdSe / CdS core-shell semiconductor nanocrystals obtained in Example 1 at three excitation wavelengths, Fig.15 (b) shows the photoexcitation spectra of the nanosheets obtained in Example 1 at three excitation wavelengths.

[0056] Fig.16 The UV-Vis and fluorescence emission (PL) spectra of the nanosheets obtained in Example 2 and the corresponding CdSe / CdS core-shell semiconductor nanocrystals are shown.

[0057] Fig.17 The UV-Vis, fluorescence emission (PL) spectra and photoexcitation spectra of the nanosheets obtained in Example 3 are shown.

[0058] Fig.18 The HAADF top view of the nanosheet obtained in Example 3 is shown. DETAILED DESCRIPTION

[0059] It should be noted that the following detailed descriptions are all illustrative and are intended to provide further explanation of the present disclosure. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present disclosure belongs.

[0060] Although the terms "first", "second", "third", etc. may be used herein to describe various elements and components, these elements and components should not be limited by these terms. These terms are only used to distinguish one element or component from another element or component.

[0061] According to a first aspect of the present disclosure, a nanosheet is provided, comprising a plurality of spaced-apart semiconductor nanocrystals and a matrix in which the plurality of semiconductor nanocrystals are dispersed, wherein the material of the semiconductor nanocrystals is a first semiconductor compound, the material of the matrix is ​​a second semiconductor compound, and the matrix is ​​a continuous single crystal material.

[0062] The semiconductor nanocrystals are dispersed in a two-dimensional crystal (or matrix) at intervals, and the second semiconductor compound formed by epitaxy is not only continuous and complete without voids, but also has good crystal quality and is in a single crystal state. Such a matrix crystal limits the spatial distribution of electrons and holes in the semiconductor nanocrystals on the one hand, and also provides a basis for quantum coupling between semiconductor nanocrystals. Generally, semiconductor nanocrystals have uneven optical properties due to uneven size, uneven surrounding chemical environment, uneven structural environment, etc., but the newly formed nanosheets disclosed in the present invention achieve the characteristics of uniform optical properties. The aforementioned optical properties refer to the peak position of fluorescence emission, half-peak width, etc. It is speculated that each semiconductor nanocrystal in the nanosheet has a common set of band structures due to quantum coupling, eliminating the differences in the energy bands of a single semiconductor nanocrystal, so that the optical properties of dozens or even hundreds of semiconductor nanocrystals in the nanosheet are almost the same.

[0063] In some embodiments, the second semiconductor compound has a different bandgap width from the first semiconductor compound. In some embodiments, the conduction band of the second semiconductor compound is higher than the conduction band energy of the first semiconductor compound, ie, type I semiconductor nanocrystal.

[0064] In some embodiments, the first semiconductor compound has the same lattice structure as the second semiconductor compound, and the difference in lattice constant is less than 10%. In some embodiments, the first semiconductor compound has the same lattice structure as the second semiconductor compound, and the difference in lattice constant is less than or equal to 5%. In some embodiments, the lattices are both zinc blende structures.

[0065] In addition to being in the form of a sheet, the nanosheet has no limitation on the shape of other dimensions, and the nanosheet is not a nanorod. Examples of the first semiconductor compound material include, but are not limited to, II-VI compounds, II-V compounds, III-VI compounds, III-V compounds, IV-VI compounds, I-III-VI compounds, II-IV-VI compounds, II-IV-V compounds, and alloy compounds comprising any of the foregoing elements. Non-limiting examples of embodiments include ZnO, ZnS, ZnSe, ZnTe, CdO, CdS, CdSe, CdTe, MgS, MgSe, GaAs, GaN, GaP, GaSe, GaSb, HgO, HgS, HgSe, HgTe, InAs, InN, InP, InSb, AlAs, AlN, AlP, AlSb, TlN, TlP, TlAs, TlSb, PbO, PbS, PbSe, PbTe, Ge, Si, alloys comprising any of the foregoing, and / or mixtures comprising any of the foregoing, including ternary and quaternary mixtures or alloys.

[0066] In some preferred embodiments, the first semiconductor compound is a II-VI compound, and the second semiconductor compound is a II-VI compound. The first semiconductor compound is different from the second semiconductor compound.

[0067] In some embodiments, the first semiconductor compound is CdSe, and the second semiconductor compound is CdS. The side length of a cubic CdSe unit cell is 0.605 nm, and the side length of a cubic CdS unit cell is 0.5832 nm.

[0068] In some embodiments, the first semiconductor compound is CdSe, the second semiconductor compound is CdS, wherein the molar content of cadmium in the nanosheets is 51-55%, the molar content of S is 35-40%, and the molar content of Se is 6-9%.

[0069] In some embodiments, the first semiconductor compound is CdSe, and the second semiconductor compound is CdS, wherein the molar ratio of cadmium to (S+Se) in the nanosheets is greater than 1 and less than or equal to 1.2, or is between 1.15 and 1.2.

[0070] The surface of the nanosheet has a ligand, and the ligand compound can be any suitable ligand compound known in the art without particular limitation. The surface ligand can be directly synthesized or obtained through ligand exchange. For example, the ligand compound may include the formula RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, RH 2 PO, R 2 HPO, R 3PO, RH 2 P.R 2 HP, R 3 P, ROH, RCOOR', RPO(OH) 2 or R 2 Compounds of POOH, wherein R and R' are independently C1-C24 alkyl, C2-C24 alkenyl, or C6-C20 aryl, or a combination thereof. The organic ligand compound can coordinate to the surface of the nanocrystal as prepared, enhance the dispersion of the nanocrystal in the solution, and it can have an effect on the luminescence and electrical properties of the nanocrystal. Examples of the organic ligand compound may include, but are not limited to, methyl mercaptan, ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, octyl mercaptan, dodecanethiol, hexadecyl mercaptan, octadecyl mercaptan, benzyl mercaptan, methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, octylamine, dodecylamine, hexadecylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine, formic acid, acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecyl acid, oleic acid, benzoic acid, phosphine such as substituted or unsubstituted methyl phosphine (e.g., trimethyl phosphine, methyl diphenyl phosphine, etc.), substituted or unsubstituted ethyl phosphine (e.g., triethyl phosphine, ethyl diphenyl phosphine, etc. ), substituted or unsubstituted propyl phosphine, substituted or unsubstituted butyl phosphine, substituted or unsubstituted pentyl phosphine, substituted or unsubstituted octyl phosphine (e.g., trioctyl phosphine), etc., phosphine oxide compounds such as substituted or unsubstituted methyl phosphine oxide (e.g., trimethyl phosphine oxide, methyl diphenyl phosphine oxide, etc.), substituted or unsubstituted ethyl phosphine oxide (e.g., triethyl phosphine oxide, ethyl diphenyl phosphine oxide, etc.), substituted or unsubstituted propyl phosphine oxide, substituted or unsubstituted butyl phosphine oxide, substituted or unsubstituted octyl phosphine oxide (e.g., trioctyl phosphine oxide, etc.), diphenyl phosphine compounds, triphenyl phosphine compounds, oxide compounds thereof, etc., and phosphonic acid. The organic ligand compound can be used alone or as a combination of at least two of the aforementioned compounds. It is generally believed that there is no ligand on the surface of semiconductor nanocrystals dispersed in the matrix.

[0071] In some embodiments, the spacing between adjacent semiconductor nanocrystals is substantially equal, and substantially equal means that the deviation is within 15%. In some embodiments, the spacing between adjacent semiconductor nanocrystals is 1.2 to 3 nm. The spacing can be adjusted by the preparation method.

[0072] In some embodiments, the thickness of the nanosheet is in the range of 1.5 to 2.5 nm, and the lateral size of the nanosheet is in the range of 10 to 50 nm. The lateral size refers to the longer side length of the lateral surface, which is the two sides of the nanosheet with the largest area. The area of ​​the lateral surface can reach 2000 nm. 2 In a preferred embodiment, the lateral surface of the nanosheet is flat, and can be flat at the atomic level.

[0073] In some embodiments, the thickness of the nanosheet is <001> The directions include 6 to 7 monolayers of Cd and 5 monolayers of Se / S, where “ / ” represents the combined calculation of Se and S layers.

[0074] The fluorescence emission peak position of the nanosheet can be achieved by adjusting the process as needed. In some embodiments, the fluorescence emission peak position of the nanosheet is between 500 and 520 nm.

[0075] In some embodiments, the ultraviolet-visible absorption spectrum of the nanosheet includes a two-dimensional morphology absorption peak of the second semiconductor compound and a zero-dimensional morphology absorption peak of the first semiconductor compound. In some embodiments, the ultraviolet-visible absorption spectrum of the nanosheet includes three ultraviolet-visible absorption peaks. In some embodiments, depending on the specific composition of the specific nanosheet, the three ultraviolet-visible absorption peaks are in the range of 495-505nm, 430-440nm, and 405-415nm, respectively.

[0076] The larger the size of the nanosheet, the larger the number of semiconductor nanocrystal particles. In some embodiments, the number of semiconductor nanocrystal particles in the nanosheet is 10 to 1000, or 20 to 500.

[0077] In some embodiments, the fluorescence efficiency of the nanosheet is greater than or equal to 50%, and the half-peak width is less than or equal to 105 meV. The fluorescence efficiency and half-peak width can be improved according to the synthesis scheme. In some embodiments, the fluorescence efficiency of the nanosheet is greater than or equal to 70%, or greater than or equal to 85%, or greater than or equal to 95%.

[0078] In some embodiments, the nanosheets have a zinc blende structure.

[0079] In some embodiments, the semiconductor nanocrystals in the nanosheets are spherical or non-spherical, and the average size of the semiconductor nanocrystals may be 1 to 20 nm, 1 to 10 nm, or 1 to 5 nm. When the semiconductor nanocrystals have a spherical shape, the size of the semiconductor nanocrystals may be a diameter. When the semiconductor nanocrystals are non-spherical, the size of the semiconductor nanocrystals may be the diameter of a circle of equivalent (equal) area calculated from the two-dimensional area of ​​the electron microscope image of the semiconductor nanocrystals.

[0080] In some embodiments, the semiconductor nanocrystal in the nanosheet is a core-shell semiconductor nanocrystal, including a semiconductor nanocrystal core and at least one shell layer, the material in the semiconductor nanocrystal excluding the outermost shell layer is a first semiconductor compound, and the material of the outermost shell layer is the same as the material of the matrix. In some embodiments, the first exciton absorption peak of the semiconductor nanocrystal core in the core-shell semiconductor nanocrystal is between 430 and 450 nm, and the first exciton absorption peak of the core-shell semiconductor nanocrystal is between 470 and 490 nm. In some embodiments, the semiconductor nanocrystal core is a sphalerite structure. In some embodiments, the size of the semiconductor nanocrystal core is less than or equal to 2.5 nm, and the size of the core-shell semiconductor nanocrystal is less than or equal to 3.5 nm. In some embodiments, the core-shell semiconductor nanocrystal has a shell of 1 to 3 monolayers. The above characteristics are difficult to detect according to the prior art, but can be determined by the control parameters in the preparation method of the nanosheet.

[0081] The above nanosheets have a superlattice structure, which is also difficult to characterize. It can be preliminarily explained by using a color-coded element distribution diagram. For example, in CdSe / CdS superlattice nanosheets, Se elements are relatively dispersed because they exist in semiconductor nanocrystals, while S elements, as a component element of the matrix, are distributed more continuously and appear to be a whole sheet. However, theoretical analysis can be performed through the preparation method of the nanosheets.

[0082] According to a second aspect of the present disclosure, an optoelectronic device is provided, comprising any one of the above nanosheets. The optoelectronic device may be a light emitting diode lighting device, an electroluminescent display device, a solar cell, an image sensor, a laser, and the like.

[0083] According to a third aspect of the present disclosure, a nanosheet dispersion is provided, comprising a plurality of any one of the above nanosheets and a dispersion medium.

[0084] In some embodiments, the thickness deviation between each nanosheet is within 10%.Through the control of the wet chemical process, the thickness distribution of the nanosheet can be effectively controlled.

[0085] In some embodiments, the lateral dimensions of the individual nanosheets are different but range from 10-50 nm.

[0086] In some embodiments, the mass fraction of the nanosheets in the dispersion is greater than or equal to 0.1wt%, or greater than or equal to 1wt%, or greater than or equal to 5wt%. In some embodiments, the dispersion medium is selected from one or more of a polymerizable monomer, hexane, heptane, octane, chloroform, ODE, toluene and benzene. The above-mentioned dispersion may also include a thermal initiator or a photoinitiator.

[0087] According to the fourth aspect of the present disclosure, a method for preparing a nanosheet is provided, the method comprising: preparing a stock solution containing a plurality of semiconductor nanocrystal cores of a first semiconductor compound; mixing the stock solution of the semiconductor nanocrystal cores and the raw material of the second semiconductor compound shell layer and heating the mixture to react, thereby epitaxially growing the second semiconductor compound shell layer on the surface of each semiconductor nanocrystal core to obtain a core-shell semiconductor nanocrystal; using the raw material of the second semiconductor compound shell layer to achieve directional two-dimensional connection of each core-shell semiconductor nanocrystal to obtain a nanosheet. It should be noted that the directional two-dimensional connection and the formation of the core-shell semiconductor nanocrystal can be carried out simultaneously, or the process of epitaxial growth of the shell layer and the two-dimensional connection can be ignored, and of course there can also be an artificial stage-by-stage distinction.

[0088] The above method completes the two-dimensional directional connection of pre-synthesized core-shell semiconductor nanocrystals in the reaction solution, and synthesizes nanosheets with a superlattice structure in the solution. In addition to providing spatial confinement for the exciton state of CdSe semiconductor nanocrystals in the two-dimensional superlattice, the epitaxially grown nanosheets are in a continuous single crystal state, dense and void-free, which better realizes the quantum coupling between semiconductor nanocrystals, thereby providing uniform optical properties of the two-dimensional superlattice. Moreover, the difference in optical properties between each nanosheet is also very small. The results show that solution synthesis can provide a simple method to obtain semiconductor superlattices with unique but complex electronic structures, which is difficult to achieve with other preparation methods. The above "superlattice" is used to describe the orderly assembly of solution-synthesized nanocrystals, and there is electronic coupling between nanocrystals. It should be noted that not all semiconductor nanocrystals grow into nanosheets in the above preparation method, and of course it is preferred that all semiconductor nanocrystals grow into nanosheets.

[0089] In some embodiments, according to the above preparation method, specifically, the preparation method includes:

[0090] S1, mixing a core cation precursor, a core anion precursor, an optional first ligand and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of multiple semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound;

[0091] S2, mixing a stock solution of semiconductor nanocrystal core, a shell cation precursor, a shell anion precursor, an optional second ligand, and a second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the second dispersion to obtain core-shell semiconductor nanocrystals, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the shell material is a second semiconductor compound;

[0092] S3, mixing the stock solution of core-shell semiconductor nanocrystals, the two-dimensional connection cationic precursor and the optional third ligand, reacting at a third temperature for a certain time, so that each core-shell semiconductor nanocrystal is two-dimensionally connected through the second semiconductor compound, and obtaining a third dispersion containing nanosheets; wherein the cation in the two-dimensional connection cationic precursor is the cation in the second semiconductor compound. It should be noted that in other embodiments, S2 and S3 may not be distinguished, that is, they are one step, that is, S3 can be omitted by adjusting the amount of raw materials of S2, without adding additional cationic precursors and optional third ligands.

[0093] In some embodiments, the conduction band energy of the second semiconductor compound is higher than the conduction band energy of the first semiconductor compound, that is, type I semiconductor nanocrystals are obtained.

[0094] "Optional" means that a ligand may or may not be added, and the first ligand, the second ligand and the third ligand may be ligands known in the art, and preferably the first ligand, the second ligand and the third ligand are fatty acids with less than 24 carbon atoms. In some preferred embodiments, the second ligand is not added to S2.

[0095] The precursor raw material is selected according to the semiconductor material to be synthesized, without particular limitation. Examples of the first semiconductor compound material include, but are not limited to, II-VI compounds, II-V compounds, III-VI compounds, III-V compounds, IV-VI compounds, I-III-VI compounds, II-IV-VI compounds, II-IV-V compounds, and alloy compounds comprising any of the aforementioned elements. Non-limiting examples of embodiments include ZnO, ZnS, ZnSe, ZnTe, CdO, CdS, CdSe, CdTe, MgS, MgSe, GaAs, GaN, GaP, GaSe, GaSb, HgO, HgS, HgSe, HgTe, InAs, InN, InP, InSb, AlAs, AlN, AlP, AlSb, TiN, TiP, TiAs, TiSb, PbO, PbS, PbSe, PbTe, Ge, Si, alloys comprising any of the foregoing, and / or mixtures comprising any of the foregoing, including ternary and quaternary mixtures or alloys.

[0096] In some preferred embodiments, the first semiconductor compound is a II-VI compound, and the second semiconductor compound is a II-VI compound. The first semiconductor compound is different from the second semiconductor compound. In some preferred embodiments, the first semiconductor compound and the second semiconductor compound have the same lattice structure, and the difference in lattice constant is less than 10%.

[0097] The organic reaction medium used in the method of the embodiment is not specifically limited and may include any suitable organic reaction medium that can be used to prepare semiconductor nanocrystals. Examples of organic reaction media may include: C6 to C22 primary amines, such as hexadecylamine; C6 to C22 secondary amines, such as dioctylamine; C6 to C40 tertiary amines, such as trioctylamine; nitrogen-containing heterocyclic compounds, such as pyridine; C6 to C40 aliphatic hydrocarbons (e.g., alkanes, alkenes, alkynes, etc.), such as hexadecane, octadecane, octadecene or squalane; C6 to C30 aromatic hydrocarbons, such as phenyldodecane, phenyltetradecane or phenylhexadecane; phosphine substituted with C6 to C22 alkyl, such as trioctylphosphine; phosphine oxide substituted with C6 to C22 alkyl, such as trioctylphosphine oxide; C12 to C22 aromatic ethers, such as phenyl ether or benzyl ether; or combinations thereof, but not limited thereto. The "liquid" for dispersing the semiconductor nanocrystal core or core-shell semiconductor nanocrystal above can be selected with reference to the range of organic reaction media.

[0098] The reaction time is not specifically limited, but can be appropriately selected. For example, the reaction can be performed for, for example, greater than or equal to about 20 minutes or greater than or equal to about 25 minutes, but it is not limited thereto. The reaction can be performed in an inert gas atmosphere or air or under vacuum, but it is not limited thereto.

[0099] In some embodiments, the preparation method further comprises S4: separating and purifying the third dispersion to obtain nanosheets. The separation and purification method is not particularly limited, and a specific solvent can be added to the liquid of the reaction product, and separation can be performed by centrifugation, precipitation, chromatography or distillation.

[0100] In some embodiments, in S3, the cationic precursor and the optional third ligand are heated to a third temperature and injected into the stock solution of the core-shell semiconductor nanocrystals for mixing and reaction.

[0101] In some embodiments, in S3, the photoluminescence peak position of the product during the reaction process does not blue shift. It can be known that the luminescence peak position shifts due to the lack of formation of alloy nanocrystals of the first semiconductor compound and the second semiconductor compound. This proves that there is no obvious alloying, dissolution or maturation during the directional attachment process.

[0102] In some preferred embodiments, the cation precursor in S3 is a metal acetate and the third ligand is oleic acid.

[0103] Temperature has an effect on the reaction product. In some preferred embodiments, the first temperature ranges from 210 to 260° C., the second temperature ranges from 170 to 190° C., and the third temperature ranges from 215 to 250° C., thereby obtaining nanosheets with high optical properties.

[0104] In order to obtain high-quality nanosheets, the shell growth of S2 should reduce or reduce the probability of self-nucleation, which can be controlled by adjusting the raw material ratio. In some embodiments, the molar ratio of the shell cation precursor (calculated as cation) to the shell anion precursor (calculated as anion) in S2 is 5:4 to 5:1. In other embodiments, the molar ratio of each raw material in S2 is as follows: the molar ratio of the semiconductor nanocrystal to the shell cation precursor (calculated as cation) in the stock solution containing the semiconductor nanocrystal core is 1:50 to 1:200. In other embodiments, in some embodiments, the molar ratio of the shell cation precursor (calculated as cation) to the shell anion precursor (calculated as anion) in S2 is 1 to 2.

[0105] In some embodiments, in S3: a stock solution containing core-shell semiconductor nanocrystals, an anion precursor, a cationic precursor and a fatty acid are mixed and reacted at a third temperature to obtain a third dispersion containing nanosheets, wherein the anion in the anion precursor is the anion in the second semiconductor compound.

[0106] In some embodiments, the preparation method further comprises optimizing the surface of the nanosheet to reduce surface defects of the nanosheet and improve the optical properties of the nanosheet.

[0107] In some embodiments, the first exciton absorption peak of the semiconductor nanocrystal core is between 430 and 450 nm, and the first exciton absorption peak of the core-shell semiconductor nanocrystal is between 470 and 490 nm. The first exciton absorption peak can represent the size, and nanosheets with high optical properties are easily obtained within this size range.

[0108] In some embodiments, the size of the semiconductor nanocrystal core is less than or equal to 2.5 nm, and the size of the core-shell semiconductor nanocrystal is less than or equal to 3.5 nm, thereby obtaining a nanosheet with high optical performance. It is easy to obtain a nanosheet with high optical performance within this size range.

[0109] In some embodiments, the core-shell semiconductor nanocrystal has a shell of 1 to 3 monolayers.

[0110] In some preferred embodiments, the conduction band of the shell layer is higher than the conduction band energy of the semiconductor nanocrystal core, and the semiconductor nanocrystal core has a zinc blende structure.

[0111] In some embodiments, the fluorescence emission peak position of the nanosheet can be adjusted by adjusting one or both of the size of the semiconductor nanocrystal core and the shell thickness of the core-shell semiconductor nanocrystal.

[0112] Hereinafter, the embodiments are described in more detail with reference to specific examples. However, they are illustrative examples of the present disclosure, and the present disclosure is not limited thereto.

[0113] Chemicals: Selenium powder (Se, 200 mesh, 99.999%), 1-octadecene (ODE, 90%), oleic acid (90%), oleylamine (≥98%), cadmium acetate dihydrate (Cd(Ac) 2 ·2H 2 O, 98+%) was purchased from Sigma Aldrich. Cadmium acetate dihydrate (Cd(Ac) 2 ·2H 2 O, 99.999%) and sulfur powder (S, 99.98%) were purchased from Alfa Essar. Stearic acid (90%) was purchased from Tokyo Chemical Industry Co., Ltd. Acetone (analytical reagent), anhydrous methanol, chloroform (analytical reagent), and toluene (analytical reagent) were purchased from Sinopharm Chemical Reagent. All chemicals were used without further purification.

[0114] Preparation of anion precursor solutions / suspensions. Selenium powder (1 mmol) was dispersed in 20 mL ODE as a Se suspension. S-ODE solution was prepared by dissolving S powder (0.9 mmol) in 15 mL ODE by ultrasonication at room temperature and stored in dark conditions before use.

[0115] Preparation of cadmium precursor solution. Under argon bubbling for 10 min, cadmium acetate dihydrate (0.9 mmol), oleic acid (0.4 mmol) and 16 mL of ODE were loaded into a 25 mL three-necked flask and heated to 170 ° C for 5 min. The mixture was cooled to room temperature in air. After centrifugation at 10000 rpm for 4 min, the supernatant (about 16 mL) was obtained as the cadmium precursor solution. The solution should be freshly prepared.

[0116] Synthesis of cadmium stearate. Dissolve cadmium acetate dihydrate (10 mmol) in methanol (50 mL) in a 100 mL beaker. In another beaker (500 mL), dissolve stearic acid (20 mmol) and tetramethylammonium hydroxide (20 mmol) in 200 mL methanol by stirring for 20 min. Drop the cadmium acetate solution into the 500 mL beaker. Cadmium stearate is a white precipitate. After adding the cadmium acetate solution, continue stirring for 20 min. Separate the precipitate by filtration and wash three times with methanol. The final precipitate is vacuum dried overnight at room temperature before use.

[0117] Example 1

[0118] Synthesis and purification of CdSe core quantum dots. In a typical synthesis, cadmium stearate (0.1 mmol) and ODE (4 mL) were charged into a 25 mL three-necked flask. After stirring and degassing by argon bubbling for 10 min, the mixture in the flask was heated to 240 ° C under argon protection. After vigorous shaking, the Se suspension (1 mL) was quickly injected, and after waiting for 10 s, the heating device was quickly removed and the reaction mixture was quickly cooled to room temperature by a blower. The reaction mixture was centrifuged at 12000 rpm for 4 min to remove ODE and free fatty acids in the supernatant. The precipitate of core quantum dots and cadmium stearate was mixed with 2 mL of chloroform. After shaking by vortex, oleylamine was dropped into the mixture to obtain a clear solution by dissolving cadmium stearate and quantum dots. In order to further improve the dissolution of cadmium carboxylate, about 0.2 mL of oleic acid was added to the solution. The solution was centrifuged at 12000 rpm for 4 min to remove any residual selenium powder in the precipitate. A mixture of methanol and acetone (volume ratio of 1:5) was added to the supernatant to precipitate the quantum dots. After centrifugation at 12000rpm for 5min, the precipitate was collected and mixed with 2mL of chloroform and 0.3mL of oleic acid. The operation of removing cadmium stearate (including adding oleylamine to obtain a clear solution, adding a mixture of methanol and acetone to precipitate the quantum dots, centrifuging and decanting to separate the quantum dots, and dissolving the precipitate in chloroform) was repeated to remove a large amount of excess cadmium stearate. The removal operation was repeated without adding oleylamine until the precipitate was easily dissolved in chloroform by adding only about 0.2mL of oleic acid (without adding oleylamine). Finally, when the precipitate can be easily dissolved in chloroform without adding oleic acid, the purification of the quantum dots is completed.

[0119] Synthesis and purification of CdSe / CdS core-shell quantum dots. The purified CdSe core quantum dots were mixed with 4 mL of cadmium stearate and 1 mL of S-ODE solution (0.06 M) in a 50 mL three-necked flask. After stirring and degassing by argon bubbling for 10 min, the mixture in the flask was heated to 180 ° C under argon protection for initial shell growth. After the UV-visible spectrum peak moved about 15 nm relative to the CdSe core quantum dots, in order to further epitaxially grow the CdS shell, a 4:1 (volume ratio) mixture of cadmium stearate and S-ODE solution was added at 180 ° C until the specified shell thickness was grown, which was monitored by UV-visible spectroscopy measurement. The absorption peak of the UV-visible absorption spectrum was red-shifted from 450 nm to 490 nm to stop the reaction. The addition rate of the mixed precursor solution was about 0.7 mL / min. After cooling in air, the final reaction mixture was mixed with an equal amount of acetone and centrifuged at 12000 rpm for 5 min. The precipitate was separated by decantation and purified using similar procedures as described above for core quantum dots. The purified core-shell quantum dots were dissolved in 2 mL of ODE as a stock solution for the synthesis of CdSe@CdS superlattice nanosheets. The “@” only indicates a distinction, in CdSe@CdS, the nanosheets exist in two compounds.

[0120] Synthesis and purification of CdSe@CdS superlattice nanosheets. Cadmium acetate dihydrate (0.3 mmol), oleic acid (0.1 mmol) and ODE (8 mL) were charged into a 25 mL three-necked flask. After stirring and bubbling for 10 min, the mixture in the flask was heated to 235 °C under argon. The purified core-shell quantum dot stock solution (1 mL, at room temperature) was quickly injected into the flask. The temperature was set to 235 °C for the specified time. The reaction was monitored by UV-visible spectroscopy and photoluminescence measurements. To stop the reaction, the reaction mixture was allowed to cool in air. When it cooled to about 150 °C, about 0.3 mL of oleic acid was injected into the flask, and the mixture was further cooled to room temperature. The separation of superlattice nanosheets was carried out by adding acetone to the reaction mixture and size-selective precipitation, and centrifugation was usually performed at 12000 rpm for 4 min.

[0121] Example 2

[0122] The difference between the experimental steps and Example 1 is:

[0123] Compared with Example 1, the reaction time in the synthesis of CdSe core quantum dots is shorter, that is, after vigorous shaking, the Se suspension (1 mL) is quickly injected and the heating device is quickly removed.

[0124] In the synthesis of CdSe / CdS core-shell quantum dots, after adding a 4:1 (volume ratio) mixture of 1.5 times the cadmium precursor solution of Example 1 and S-ODE solution at 180°C, the reaction time for shell formation is longer, and the absorption peak of the UV-visible absorption spectrum red-shifts from 433nm to 483nm and can be stopped.

[0125] Example 3

[0126] The difference between the experimental steps and Example 1 is that S is added during the synthesis of CdSe / CdS core-shell quantum dots.

[0127] Purified CdSe core quantum dots were mixed with 8 mL of cadmium precursor solution and 2 mL of S-ODE solution (0.06 M) in a 50 mL three-necked flask. After stirring and degassing by argon bubbling for 10 min, the mixture in the flask was heated to 180 ° C under argon protection for initial shell growth. After the UV-visible spectrum peak moved about 15 nm relative to the CdSe core quantum dots, the reaction was stopped and the flask was quickly cooled to room temperature with a cold air gun. Cadmium acetate (0.1 mmol) was introduced at room temperature, and the temperature was heated to 240 ° C after degassing with argon bubbling for 10 min. The reaction was monitored in real time by absorption and fluorescence spectra. The reaction was stopped after a few minutes (less than 20 min) and cooled to room temperature.

[0128] Comparative Example

[0129] 5.5 Preparation of Monolayer CdS Nanosheets

[0130] Cd(St) 2 (0.1356 g, 0.2 mmol), S-ODE (2.0032 g, 0.1 mmol S), and 6.0 g ODE were bubbled under argon for 10 min, then heated from room temperature to 190 ° C within 8 min, and kept at this temperature for 8 min to obtain spherical CdS nanocrystals with a UV-visible absorption peak at 322 nm. After cooling to room temperature, 0.1066 g Cd(Ac) was added 2 ·2H 2 O (0.4 mmol), the solution was bubbled with argon for 10 min, then heated from room temperature to 250 °C within 15 min and maintained at 250 °C for 1 min.

[0131] The above-mentioned specific embodiments provide superlattice nanosheets derived from colloidal semiconductor nanocrystals, which can be synthesized in solution, rather than relying on the self-assembly and fusion of quantum dots on a substrate as in the prior art. Through the two-dimensional directional attachment of CdSe / CdS core-shell quantum dots grown epitaxially in solution, tens to hundreds of CdSe quantum dots can be epitaxially integrated into single-crystal CdS nanosheets, and the distance between quantum dots can be controlled. The control of quantum dot size and quantum dot spacing in the superlattice is achieved through the following synthesis steps. First, zinc blende CdSe core quantum dots with controllable size are synthesized, and their first exciton absorption peak is between 430 and 450nm. CdSe quantum dots within this size range can be adjusted in shape under reaction conditions, and under relatively long-term heating conditions, CdSe nanosheets (thickness ( <001> ) direction is exactly 3 layers of selenium monolayers and 4 layers of cadmium monolayers). Then, 1 to 3 layers of CdS shell are epitaxially coated on the purified CdSe core quantum dots to form CdSe / CdS core-shell quantum dots. The conduction band (valence band) energy of CdS is higher (lower) than that of CdSe. Therefore, the epitaxial CdS shell provides the required exciton space confinement for CdSe quantum dots. Through the growth of the shell, the electron and hole wave functions are significantly delocalized into the CdS shell, which can be proved by the obvious red shift of the first exciton absorption peak to 470-490nm. Figure 2 and Figure 3 The optical and structural properties of typical CdSe core and CdSe / CdS core-shell quantum dots of Example 1.

[0132] Unless otherwise specified, the following analysis is based on the superlattice nanosheet prepared in Example 1.

[0133] Figure 4 The reaction evolution from CdSe / CdS core / shell quantum dots to superlattice nanosheets is shown. Figure 4 High-angle annular dark field (HAADF) electron microscopy measurements show that when the purified core-shell quantum dots are exposed to cadmium acetate (Cd(Ac) 2 ) and oleic acid (HOl) solution, the CdSe / CdS core-shell quantum dots with point shape (such as Figure 3 ) gradually disappears and large nanosheets with uniform contrast are produced. After reaction time > 400 s, more than 50% of the CdSe / CdS core-shell quantum dots are converted into nanosheets, and a portion of large nanocrystals can be formed by three-dimensional attachment of core-shell quantum dots. Intermediate products with two-dimensional oriented attachment can be observed in the early stage (see Figure 4 below). Figure 5 The temporal evolution of the absorption and fluorescence emission spectra of the reaction mixture during oriented attachment is shown. For comparison, Figure 5 All UV-Vis spectra in the table are taken with the same concentration of pristine core-shell QDs. Fig.13As can be seen from the dashed line, consistent with the formation of superlattice nanosheets, the two absorption peaks of the comparative CdS nanosheets appear between the wavelength range of 410nm and 440nm and dominate the absorption spectrum. Figure 5 As shown by the dashed line, the first exciton absorption of CdSe / CdS core-shell quantum dots decreases rapidly on the absorption peak and eventually turns into a weak flat shoulder, accompanied by a slight red shift in the photoluminescence peak. The temporal evolution of the optical properties is consistent with the formation of superlattice nanosheets. In addition, there should be no obvious alloying or dissolution or ripening during the oriented attachment process, because no blue shift in the photoluminescence peak was observed during this process.

[0134] Figure 6 and Figure 7 Representative top-down and atomic-resolution HAADF side-on images of superlattice nanosheets are shown. Figure 6 (a)) and the associated FFT pattern ( Figure 8 ) show that the nanosheets formed by directional attachment are located in an atomically coherent zinc blende structure lattice with the axis <001> Thickness direction. Side view ( Figure 6 (b)) shows that along the thickness direction ( <001> )'s lattice is filled with six monolayers of cadmium atoms, and some parts of the lattice may contain seven monolayers of cadmium atoms. Figure 7 (a) All nanosheets in the top view have the same <100> Zone axes, a feature that is expected for nanosheets with very large and flat basal surfaces and thin thickness. Clearly, there are no voids in the top view of the superlattice nanosheet. Figure 7 (b) Side view showing that most nanosheets have 6 layers of cadmium atoms in the thickness direction, although some of them have an additional layer of cadmium atoms. With cadmium oleate as the only ligand, both basal planes (side and top) should be terminated with cadmium atoms, indicating that the thickness <001> The direction is filled alternately with 6 monolayers of Cd and 5 monolayers of Se / S. The elemental distribution of Cd, S, and Se was measured using electron energy loss spectroscopy. Cd and S are evenly distributed, and Se is slightly aggregated in the nanosheets ( Fig. 9 The overall elemental composition of the fused nanosheets was measured using an energy dispersive spectrometer (the molar ratio results are shown in Table 1).

[0135] Table 1

[0136] Se(%) S(%) Cd(%) nuclear 44.4 / 55.6 Core-shell quantum dots 11.1 35.0 53.9 Superlattice nanosheets 8.0 38.4 53.6

[0137] The lateral size (including 1.5 monolayer CdS shell, CdSe core is 1.8nm, Figure 3 ), the thickness of the nanosheet ( Figure 6(b)) and Se / S ratio (core, core-shell quantum dots and superlattice, Table 1) are consistent with the two-dimensional superlattice structure. Based on the average value of the above data, the structure of the superlattice nanosheet is theoretically analyzed as follows: each CdSe quantum dot has a lateral size of about 1.8nm, has 3 Se monolayers along the thickness direction, is epitaxially connected to the adjacent quantum dots through about 3 monolayers of CdS lattice, and is covered with about 1 CdS monolayer on each of the two basal planes ( Fig.10 For a superlattice of typical size (lateral dimension of about 20nm), one superlattice nanosheet contains about 55 CdSe quantum dots in its epitaxial layer.

[0138] Since the original core-shell nanocrystals ( Figure 3 ) and three-dimensional fused nanocrystals (i.e., the large-sized dot-like nanocrystals of the byproduct of the three-dimensional directional attachment mentioned above) are different from the superlattice in size and shape, so the colloidal CdSe@CdS superlattice nanosheets can be easily separated from the reaction solution and other small parts. Z contrast image of purified CdSe@CdS superlattice nanosheets ( Fig.11 The inset of Figure 3 shows that the superlattice nanosheets have uniform thickness and a wide distribution of lateral sizes (10 to 50 nm). Fig.11 X-ray diffraction measurements in the literature show that the purified 2D superlattice has a diffraction pattern similar to that of a 5.5 monolayer CdS nanosheet (along <001> There are exactly 6 Cd monolayers and 5 S monolayers in the thickness direction). Fig.11 Because about 20% of the anions in the CdSe@CdS superlattice nanosheet are Se, the entire diffraction pattern of the superlattice nanosheet is shifted to the low-angle direction compared to the 5.5 monolayer CdS nanosheet of the comparative example. Since the zinc-blende structured nanosheet has a finite thickness and an atomically flat basal plane, its diffraction pattern is significantly different from the standard diffraction pattern. The most notable feature of this particular thickness is Fig.11 Two unexpected peaks in the middle circle. The nanosheet has a flat surface and only a few layers of atoms in the thickness direction, which is different from the face-centered cubic unit cell in the bulk phase and is more suitable to be viewed as a tetragonal unit cell.

[0139] Fig.12 (a) Comparison of UV-visible absorption spectra of pristine CdSe / CdS core-shell quantum dots and purified 2D CdSe@CdS superlattice nanosheets (same cadmium atomic concentration in the test solution). The absorption spectrum of core-shell quantum dots is dominated by the first exciton absorption peak, similar to typical CdSe / CdS core-shell quantum dots, while the absorption spectrum of 2D CdSe@CdS superlattice nanosheets undergoes a dramatic change. The superlattice nanosheets exhibit two strong and sharp absorption peaks at approximately 435nm and 410nm, which are almost identical to the absorption peaks of the comparative CdS nanosheets (see Fig.13). Upon forming a superlattice nanosheet, the first exciton absorption peak reduces its absorbance by 90%. These huge differences between the original core-shell quantum dots and the superlattice nanosheets are caused by two independent factors. First, the unit extinction coefficient of the CdS nanosheet with thin thickness and large lateral size should be much larger than that of the CdS shell (or spherical CdS quantum dots). Second, the band-edge electron and hole wave functions between all CdSe quantum dots in the entire superlattice nanosheet are coupled, and the electron wave functions should be more delocalized due to their smaller effective mass. The extensive but inhomogeneous delocalized band-edge electron and hole wave functions should lead to a greatly reduced oscillation intensity of the band-edge excitons, which is somewhat similar to the spatial indirect transitions in type-II CdTe / CdSe core-shell quantum dots.

[0140] Without surface optimization, the 2D CdSe@CdS superlattice has a high photoluminescence quantum yield (about 50%). Fig.12 (b) shows that the photoluminescence spectrum of the two-dimensional CdSe@CdS superlattice nanosheet is slightly red-shifted compared to the original CdSe / CdS core-shell quantum dots, but the peak width is reduced by about 30% on the high-energy side of the peak. For the two-dimensional CdSe / CdS superlattice nanosheet, the photoluminescence spectrum of a single nanocrystal is almost the same as the spectrum of the aggregate ( Fig.14 ), indicating that there is no uneven broadening of the 2D superlattice nanosheets in the solution. This conclusion was further confirmed by photoluminescence excitation measurements at three wavelengths, namely the photoluminescence peak (denoted as peak), the peaks on both sides of the photoluminescence peak plus half the peak value (denoted as peak+λ1 / 2 and peak-λ1 / 2). Fig.15 The photoluminescence excitation spectra in (a) shift significantly with the emission wavelength, and each spectrum is Fig.12 The corresponding absorption spectrum in (a) is much narrower, revealing the inhomogeneous broadening of the photoluminescence and absorption of the pristine CdSe / CdS core-shell quantum dots. Fig.15 The three photoluminescence excitation spectra in (b) and Fig.12 The corresponding absorption spectra in (a) are almost identical in spectral profile, thus ruling out the existence of uneven broadening of the aggregate photoluminescence and absorption spectra, i.e., coupling between quantum dots is achieved in almost every nanosheet.

[0141] Although this is somewhat surprising, the elimination of inhomogeneous broadening by forming a superlattice is expected. In the nanosheet, tens to hundreds of CdSe quantum dots form a unified delocalized electron and hole microband through quantum coupling, excluding the variation of band-edge exciton energy levels between quantum dots. A certain bandwidth of the band-edge microband in the nanosheet should lead to a finite photoluminescence peak width due to the thermal distribution of band-edge excitons in the microband. In principle, the peak width of the overall and individual nanocrystal photoluminescence of the two-dimensional CdSe@CdS superlattice nanosheet (about 105meV) ( Fig.12 (b) and supplement Fig.14 ) can be considered as a rough measure of the microband bandwidth, which is about 50% wider than the peak width (about 70 meV) of a single CdSe / CdS core-shell quantum dot with a similar emission peak.

[0142] At a certain thickness, the emission peak position of the 2D CdSe@CdS superlattice nanosheet can be tuned by applying CdSe core quantum dots of different sizes and / or CdS shells of different thicknesses. Fig.16 The spectrum of Example 2 is shown. Preliminary results further show that, at a fixed CdSe core size, the distance between quantum dots within the 2D CdSe@CdS superlattice can be adjusted by dropping S precursor during the directional attachment step, see Example 3, which does not change the thickness of the 2D CdSe@CdS superlattice nanosheet but changes the coupling between the quantum dots, from Fig.17 and Fig.18 It can be seen that the average distance between CdSe quantum dots in the superlattice nanosheet will increase.

[0143] Superlattice nanosheets prepared by solution method are a new type of quantum material. Semiconductor nanocrystals (also known as quantum dots) that are quantum confined in all three-dimensional directions can be regarded as "artificial atoms", and two (or several) "artificial atoms" - especially colloidal core / shell semiconductor nanocrystals - are epitaxially fused together to form "artificial molecules". Colloidal superlattices formed by epitaxial fusion of multiple colloidal core-shell quantum dots can be regarded as "artificial polymers", similar to semiconductor polymers. But unlike "artificial atoms" and "artificial molecules", two-dimensional superlattice nanosheets can exclude inhomogeneous absorption and photoluminescence broadening. Colloidal two-dimensional superlattices with unique electronic structures will provide new options for high-performance optoelectronic devices based on colloidal semiconductor nanocrystals, such as high-brightness light-emitting diodes, solar cells and lasers.

[0144] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A nanosheet, characterized in that: The nanosheet includes a plurality of semiconductor nanocrystals distributed at intervals and a matrix in which the plurality of semiconductor nanocrystals are dispersed, the semiconductor nanocrystals are dispersed at intervals in the matrix, the material of the semiconductor nanocrystals is a first semiconductor compound, the material of the matrix is ​​a second semiconductor compound, the matrix is ​​a continuous single crystal material, the spacing between adjacent semiconductor nanocrystals is 1.2 to 3 nm, the spacing between adjacent semiconductor nanocrystals is basically equal, and basically equal means that the deviation is within 15%, the first semiconductor compound and the second semiconductor compound have the same lattice structure, and the difference in lattice constants is less than 10%.

2. The nanosheet according to claim 1, characterized in that The second semiconductor compound has a different bandgap from that of the first semiconductor compound.

3. The nanosheet according to claim 1, characterized in that The first semiconductor compound is a II-VI compound, and the second semiconductor compound is a II-VI compound.

4. The nanosheet according to claim 3, characterized in that The first semiconductor compound is CdSe, and the second semiconductor compound is CdS, wherein the molar content of cadmium in the nanosheet is 51-55%, the molar content of S is 35-40%, and the molar content of Se is 6-9%.

5. The nanosheet according to claim 3, characterized in that The thickness of the nanosheet is in the range of 1.5 to 2.5 nm, and the lateral size of the nanosheet is in the range of 10 to 50 nm.

6. The nanosheet according to claim 3, characterized in that The thickness of the nanosheet <001> The directions include 6-7 monolayers of Cd and 5 monolayers of Se / S.

7. The nanosheet according to claim 3, characterized in that The fluorescence emission peak of the nanosheet is between 500 and 520 nm.

8. The nanosheet according to claim 3, characterized in that: The ultraviolet-visible absorption spectrum of the nanosheet includes a two-dimensional morphology absorption peak of the second semiconductor compound and a zero-dimensional morphology absorption peak of the first semiconductor compound.

9. The nanosheet according to claim 1, characterized in that: The number of the semiconductor nanocrystal particles in the nanosheet is 10 to 1000.

10. The nanosheet according to any one of claims 1 to 9, characterized in that: The fluorescence efficiency of the nanosheet is greater than or equal to 50%, and the half-peak width is less than or equal to 105 meV.

11. A photoelectric device, characterized in that: The nanosheet comprises the nanosheet according to any one of claims 1 to 10.

12. A nanosheet dispersion, characterized in that: The method comprises a plurality of nanosheets according to any one of claims 1 to 10 and a dispersion medium.

13. The nanosheet dispersion according to claim 12, characterized in that: The thickness deviation between the nanosheets is within 10%.

14. A method for preparing a nanosheet according to any one of claims 1 to 10, characterized in that: The preparation method comprises: preparing a stock solution containing a plurality of semiconductor nanocrystal cores of a first semiconductor compound; mixing the stock solution of the semiconductor nanocrystal cores with a raw material of a second semiconductor compound shell layer and heating them for reaction, thereby epitaxially growing the second semiconductor compound shell layer on the surface of each semiconductor nanocrystal core to obtain a core-shell semiconductor nanocrystal; and using the raw material of the second semiconductor compound shell layer to achieve directional two-dimensional connection of each core-shell semiconductor nanocrystal to obtain the nanosheet.

15. The preparation method according to claim 14, characterized in that: The preparation method comprises: S1, mixing a core cation precursor, a core anion precursor, a first ligand and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of the semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound; S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; or S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor, the second ligand and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; S3, mixing the stock solution of the core-shell semiconductor nanocrystals, the two-dimensional connecting cation precursor and the third ligand, and reacting them at a third temperature for a certain time, so that each of the core-shell semiconductor nanocrystals is two-dimensionally connected through the second semiconductor compound, to obtain a third dispersion containing the nanosheets; wherein the cations in the two-dimensional connecting cation precursor are cations in the second semiconductor compound.

16. The preparation method according to claim 14, characterized in that: The preparation method comprises: S1, mixing a core cation precursor, a core anion precursor, a first ligand and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of the semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound; S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; or, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor, the second ligand and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; S3, mixing the stock solution of the core-shell semiconductor nanocrystals and the cationic precursor for two-dimensional connection, and reacting them at a third temperature for a certain time, so that each of the core-shell semiconductor nanocrystals is two-dimensionally connected through the second semiconductor compound, to obtain a third dispersion containing the nanosheets; wherein the cations in the cationic precursor for two-dimensional connection are cations in the second semiconductor compound.

17. The preparation method according to claim 14, characterized in that: The preparation method comprises: S1, mixing a core cation precursor, a core anion precursor and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of the semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound; S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor, the second ligand and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; or S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; S3, mixing the stock solution of the core-shell semiconductor nanocrystals, the two-dimensional connecting cation precursor and the third ligand, and reacting them at a third temperature for a certain time, so that each of the core-shell semiconductor nanocrystals is two-dimensionally connected through the second semiconductor compound, to obtain a third dispersion containing the nanosheets; wherein the cations in the two-dimensional connecting cation precursor are cations in the second semiconductor compound.

18. The preparation method according to claim 14, characterized in that: The preparation method comprises: S1, mixing a core cation precursor, a core anion precursor and a first organic reaction medium, and reacting them at a first temperature for a certain time to obtain a first dispersion containing semiconductor nanocrystal cores; separating and purifying the semiconductor nanocrystal cores from the first dispersion, dispersing the semiconductor nanocrystal cores in a liquid to obtain a stock solution of the semiconductor nanocrystal cores, wherein the material of the semiconductor nanocrystal cores is a first semiconductor compound; S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor, the second ligand and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; or S2, mixing the stock solution of the semiconductor nanocrystal core, the shell cation precursor, the shell anion precursor and the second organic reaction medium, and reacting them at a second temperature for a certain time to obtain a second dispersion containing core-shell semiconductor nanocrystals; separating and purifying the core-shell semiconductor nanocrystals from the second dispersion, dispersing the core-shell semiconductor nanocrystals in a liquid to obtain a stock solution of core-shell semiconductor nanocrystals, wherein the material of the shell layer is a second semiconductor compound; S3, mixing the stock solution of the core-shell semiconductor nanocrystals and the cationic precursor for two-dimensional connection, and reacting them at a third temperature for a certain time, so that each of the core-shell semiconductor nanocrystals is two-dimensionally connected through the second semiconductor compound, to obtain a third dispersion containing the nanosheets; wherein the cations in the cationic precursor for two-dimensional connection are cations in the second semiconductor compound.

19. The preparation method according to claim 15, 16, 17 or 18, characterized in that: The preparation method further comprises S4: separating and purifying the third dispersion to obtain nanosheets.

20. The preparation method according to claim 15 or 17, characterized in that: In S3, the cationic precursor and the third ligand are heated to a third temperature, and injected into the stock solution of the core-shell semiconductor nanocrystals to mix and react.

21. The preparation method according to claim 15, 16, 17 or 18, characterized in that: In S3, the photoluminescence peak position of the product during the reaction does not undergo a blue shift.

22. The preparation method according to claim 15, 16, 17 or 18, characterized in that: The first temperature ranges from 210 to 260°C, the second temperature ranges from 170 to 190°C, and the third temperature ranges from 215 to 250°C.

23. The preparation method according to claim 15, 16, 17 or 18, characterized in that: The molar ratio of the shell cation precursor to the shell anion precursor in S2 is 5:4 to 5:

1.

24. The preparation method according to claim 15, 16, 17 or 18, characterized in that: The molar ratio range of each raw material in S2 is as follows: the molar ratio of the semiconductor nanocrystals in the stock solution containing the semiconductor nanocrystal core to the shell cation precursor is 1:50 to 1:

200.

25. The preparation method according to claim 15, 16, 17 or 18, characterized in that: In S3, the stock solution of the core-shell semiconductor nanocrystals, the anion precursor, the cationic precursor and the fatty acid are mixed and reacted at a third temperature to obtain a third dispersion containing nanosheets, wherein the anions in the anion precursor are the anions in the second semiconductor compound.

26. The preparation method according to claim 14, characterized in that: The preparation method further comprises optimizing the surface of the nanosheet, thereby reducing surface defects of the nanosheet.

27. The preparation method according to claim 14, characterized in that: The first exciton absorption peak of the semiconductor nanocrystal core is located between 430 and 450 nm, and the first exciton absorption peak of the core-shell semiconductor nanocrystal is located between 470 and 490 nm.

28. The preparation method according to claim 14, characterized in that: The size of the semiconductor nanocrystal core is less than or equal to 2.5 nm, and the size of the core-shell semiconductor nanocrystal is less than or equal to 3.5 nm.

29. The preparation method according to claim 14, characterized in that: The core-shell semiconductor nanocrystal has a shell of 1 to 3 monolayers.

30. The preparation method according to claim 14, characterized in that: The conduction band energy of the shell layer is higher than the conduction band energy of the semiconductor nanocrystal core, and the semiconductor nanocrystal core is a zinc blende structure.

31. The preparation method according to claim 14, characterized in that: The fluorescence emission peak position of the nanosheet can be adjusted by adjusting one or both of the size of the semiconductor nanocrystal core and the shell thickness of the core-shell semiconductor nanocrystal.

Citation Information

Patent Citations

  • Photocatalyst based on quantum dot / rod and molybdenum disulfide nanosheet, preparation method thereof, photocatalysis system and hydrogen production method by reforming biomass

    CN104338547A

  • Preparation method for tin disulfide nano-sheet loading iron trioxide nano-crystalline composite nano-material

    CN104923262A

  • Composite material and preparation method thereof

    CN111359630A